Community perceptions and tourism sustainability in the Uros - Cayo-Velásquez, Noemí Emperatriz (2025)
This research explores perceptions of the sustainability of community-based tourism on the floating islands of the Uros, located on Lake Titicaca (Puno, Peru), using an interpretive qualitative ethnographic approach focused on the lived experience of local stakeholders. Semi-structured interviews and participant observation were conducted with twenty residents, whose stories were analysed using open, axial, and selective thematic coding, ensuring credibility and confirmability. Seven emerging categories were identified that reveal tensions between the desire to participate and exclusion, a concern for the care of the lake, an ethic of sustainability based on mutual respect and justice, a sense of ownership of the tourism process, impacts on everyday life, a folklorization that transforms the territory into prefabricated «postcards», and the recognition that community-based tourism can only be truly transformative when it engages its inhabitants, respects the ecological balance, and strengthens their identity, consolidating itself as a worthy tool for the wellbeing of those who care for this unique environment. Sustainability, in this context, strengthens community involvement, the recognition of local knowledge, and shared responsibility in management, which are key to moving toward a more equitable, dignified, and respectful tourism approach to the identity and territory of the Uros Islands.